Educação do campo: dificuldades encontradas pelos professores nas práticas pedagógicas nas escolas do campo no município de Inhangapi/PA - MERCÊS, Marivaldo Correa das (2019)
The present work seeks to identify the main difficulties faced in the pedagogical practice of teachers working in rural schools in the municipality of Inhangapi / PA, since new educational policies and studies in this area have already been implemented, however, they must be actually materialized in these schools. The research will be based on a reflection based on LDB 9394/96, PNE 2011-2020, PME 2015-2025, PCCR 2015 and National Guidelines for Field Education. In this sense, the means of approaches used were field research, bibliographical, documentary and internet consultation. In addition to the participation of teachers, students and pedagogical coordinators of the municipal school network, who answered some semi-structured questions, seeking to reflect on the aspects that lead to these difficulties. Thus it became important to analyze the Pedagogical Practice of the teachers of five rural schools in the municipality mentioned above, as well as the factors that trigger these difficulties.